Soil Management in the Breede River Valley Wine Grape Region, South Africa. 4. Organic Matter and Macro-nutrient Content of a Medium-textured Soil - Fourie, J.C. (South African Journal of Enology and Viticulture, 2016)
Eight cover crop treatments were applied for 12 consecutive years on a medium-textured soil (18% clay) in a vineyard near Robertson (33°50’S, 19°54’E). Full surface mulching combined with full surface chemical control from bud break to harvest (BB), i.e. T3, and no cover crop combined with BB (T2) were also applied. The control (T1) consisted of mechanical control in the work row and chemical control in the vine row from bud break to harvest. After 10 years, the %C in the 0 to 600 mm soil layer of the minimum cultivated treatments increased, except in the 0 to 300 mm soil layer, in which Festuca arundinacae was established (T11), and the 150 to 300 mm soil layer, in which Vicia dasycarpa (grazing vetch) was controlled in the vine row from bud break and in the work row from berry set (end of November) (T7). The %C in the 0 to 150 mm soil layer of the cover crop treatments also exceeded the 0.9% level above which the application of N is deemed unnecessary on these soils. During the first three years the total inorganic N in the 0 to 600 mm soil layer of the treatments in which an N-fixing cover crop was sown was higher (mostly significant) than that of T1, T2, T3 and T11 during full bloom, véraison and post-harvest. Over the medium term, grazing vetch controlled chemically on the full surface from bud break (T6) caused the total inorganic N in the 0 to 600 mm soil layer during full bloom to exceed the level at which the grapevines need additional N. During véraison, this was achieved with T7. Over the long term this was achieved during full bloom with T6 and T7. During véraison, T7 gave a similar result. T3 or the use of annuals as winter-growing cover crops may supply the fertiliser needs of the grapevines post-harvest. Although differences in the P concentration and exchangeable Ca and Mg concentrations occurred between some treatments, no significant trends were observed. The level of K in all the treatments was between two and six times higher than the optimal level for the clay loam soils in the Breede River Valley.